Analisis Manajemen Kedatangan Kapal SPOB. Indo raya - Dekanawati, Vivid; Anugrah, Kelvi; Kusuma, Ade Chandra; Astriawati, Ningrum; Subekti, Joko (Politeknik Bumi Akpelni, 2023)
The case of late ship arrival can have a very significant impact on agency service activities. Batam Kabil Liquid Bulk Port is one of the major ports on the island of Batam projected to be one of the gateways for the flow of goods to and from the island of Batam and is expected to complement the port of Singapore. For this reason, careful planning is needed so that the Kabil port can carry out its roles and functions effectively and efficiently with high performance and supported by harmonious environmental conditions. This study aims to analyse the arrival management of SPOB Ships. Indo Raya Line at Kabil Batam Liquid Bulk Port. This research is qualitative research with qualitative descriptive analysis. The data collection method in this study uses observation methods, interview methods, and documentary methods. The results showed that the analysis of the arrival time of the SPOB Ship. Indo Raya Line at Kabil Liquid Bulk Port based on 3 ship arrivals, namely arrival from Pontitributary, Guntung River, and Belinyu from the arrival process followed by anchorage to shifting with a comparison between plan and actual, a comparison of estimated time arrival (ETA) with time arrival (TA) is obtained a lot of delays.